MGA-related syndrome: A proposed novel disorder - Bobbi McGivern; Michelle M. Morrow; Erin Torti; Kirsty McWalter; Ingrid M. Wentzensen; Kristin G. Monaghan; Amanda Gerard; Laurie Robak; David Chitayat; Claire Botsford; Sarah Jurgensmeyer; Peter Leahy; et al. (HGG Advances)
Summary: MGA (OMIM: 616061) encodes a dual-specificity transcription factor that regulates the expression of Max-network and T-box family target genes, important in embryogenesis. Previous studies have linked MGA to various phenotypes, including neurodevelopmental disorders, congenital heart disease, and early-onset Parkinson’s disease. Here, we describe the clinical phenotype of individuals with de novo, heterozygous predicted loss-of-function variants in MGA, suggesting a unique disorder involving both neurodevelopmental and congenital anomalies. In addition to developmental delays, certain congenital anomalies were present in all individuals in this cohort including cardiac anomalies, male genital malformations, and craniofacial dysmorphisms. Additional findings seen in multiple individuals in this cohort include hypotonia, abnormal brain imaging, hearing loss, sleep dysfunction, urinary issues, skeletal abnormalities, and feeding difficulties. These findings provide support for MGA as a gene intolerant to protein truncation with a broad phenotypic spectrum.